Serious discordance between MTBC trace positivity by Xpert MTB/RIF ultra and follow up culture - Roy, Partha; Anand, Ankita (International Journal of Research in Medical Sciences, 2020)
Authors wish to report a major discordance between Xpert MTB/RIF Ultra Trace positivity (GeneXpert, Cepheid) and follow up by liquid culture.